2018
DOI: 10.5005/jp-journals-10024-2381
|View full text |Cite
|
Sign up to set email alerts
|

Control of Anxiety in Pediatric Patients using “Tell Show Do” Method and Audiovisual Distraction

Abstract: Introduction: Visiting a dentist can easily evoke strong fear reactions and acute anxiety in children. It is one of the most basic reasons for avoidance and neglect of dental care. It may obstruct delivery of dental care, as the child may be unwilling to accept the treatment being provided by the dentist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 21 publications
1
7
0
1
Order By: Relevance
“…Similar to this was observed with patients shown the dental song technique along, but the tell-show-do technique further exacerbated anxiety in the already anxious child with further increase in their heart rates after performing it, respectively. This corresponds to the previous studies which also fail to demonstrate any significant reduction in anxiety levels of the paediatric patients after demonstrating the "tell-showdo" technique [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to this was observed with patients shown the dental song technique along, but the tell-show-do technique further exacerbated anxiety in the already anxious child with further increase in their heart rates after performing it, respectively. This corresponds to the previous studies which also fail to demonstrate any significant reduction in anxiety levels of the paediatric patients after demonstrating the "tell-showdo" technique [26,27].…”
Section: Discussionsupporting
confidence: 90%
“…Relaxation exercises are known to boost vagal activity, increase the production of neurotransmitters against pain such as serotonin, and decrease the stress hormone levels [67]. Counter stimulation and virtual reality methods could be used to reduce pain and anxiety in the local anesthesia (LA) injection during extraction and pulp treatments [70]. VR uses fantasy worlds, and 3D real-life virtual situations with high ecological validity are more acceptable to the children [4, 66].…”
Section: Relaxation Techniques In Different Settingsmentioning
confidence: 99%
“…VR uses fantasy worlds, and 3D real-life virtual situations with high ecological validity are more acceptable to the children [4, 66]. In a recent randomized trial of 400 children by Khandelwal et al [70], it was found that audiovisual distraction is superior to the “Tell Show Do” (TSD) method in the management of anxious children aged 5–8 years [71]. Likewise, with this result, the study of Nunna et al [72] revealed a significant reduction in mean pulse rates in children who had their injection while watching cartoons under VR distraction [70].…”
Section: Relaxation Techniques In Different Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Audiovisual merupakan media penyampaian informasi terdiri dari audio (suara) dan visual (gambar) yang mencakup dua indera sekaligus yakni indera pendengaran dan indera penglihatan (Risnawati, 2018). Pemberian audiovisual khususnya kartun merupakan bentuk distraksi yang mampu mengambil kendali dengan cara menyenangkan dua jenis sensasi yaitu pada pendengaran dan visual yang pada saat bersamaan akan mengisolasi sebagian besar suara disekeliling anak dan mengisolasi pemandangan klinis yang tidak bersahabat bagi pasien anak (Tyagi, Gupta, Khatri, Khandelwal, & Kalra, 2018). Hasil studi ini didukung dengan penelitian yang dilakukan oleh (Habiba et al, 2021) yang mengungkapkan bahwa ada pengaruh distraksi video film kartun terhadap kecemasan anak dengan bronkopneumonia yang dilakukan terapi inhalasi menggunakan nebulizer.…”
Section: Pembahasanunclassified